2014
DOI: 10.1002/pat.3256
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing epoxy resin through covalent integration of functionalized graphene nanosheets

Abstract: A chemically converted graphene/epoxy (EP) resin nanocomposite has been developed through the use of the functionalized graphene nanosheets (FGNs). The FGNs were prepared via the reaction of amines with alkylcarboxyl groups attached to the graphite oxides in the course of a dicarboxylic acid acyl peroxide treatment. FGNs/EP composites were prepared by dissolving the FGNs in organic solvent followed by mixing with EP and curing agent. In this composite, the FGNs were able to create molecular entanglement with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 33 publications
(33 reference statements)
1
32
0
Order By: Relevance
“…Two peaks were detected in the N1s of GO-Al 2 O 3(Fig. 4d)at 399.7 and 401.4 eV that corresponded to C-N and N-H, respectively[40,42]. These abovementioned XPS results further demonstrated a reaction between the oxygen functional group and amine group.Combining the FT-IR and XPS analysis, we can confirm that the APTS attached to the surface of Al 2 O 3 , and GO-Al 2 O 3 has been successfully synthesized.…”
supporting
confidence: 51%
“…Two peaks were detected in the N1s of GO-Al 2 O 3(Fig. 4d)at 399.7 and 401.4 eV that corresponded to C-N and N-H, respectively[40,42]. These abovementioned XPS results further demonstrated a reaction between the oxygen functional group and amine group.Combining the FT-IR and XPS analysis, we can confirm that the APTS attached to the surface of Al 2 O 3 , and GO-Al 2 O 3 has been successfully synthesized.…”
supporting
confidence: 51%
“…The nanocomposites with the FGNPs 1.5 phr showed slightly lower T g compared to the nanocomposites with the same amount of the GNPs. This suggests that the FGNPs act as reactive plasticizers, when added over 1.0 phr, that reduce slightly the cross‐linking density of the cured epoxy matrix, thus improving slightly the flexibility of chain segments of the cross‐linked epoxy matrix …”
Section: Resultsmentioning
confidence: 99%
“…It has been vastly reported that graphene reduces the glass transition or thermal degradation temperature of epoxy matrix and there is no unanimous agreement for this negative trend. Some research groups like Saurín et al 165 , Liu et al 166 , and Guo et al 91 reported that graphene acts as reactive plasticizer and has a plasticizing effect on epoxy resin, thus increasing the flexibility of chain segments of the epoxy matrix. Graphene sheets are stiffer than epoxy matrix which could lead to significant confinement on the polymer chains.…”
Section: Thermal Stabilitymentioning
confidence: 99%